2015
DOI: 10.1021/acs.jafc.5b03306
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Immunostimulatory Activity of a Homogeneous Polysaccharide from Sinonovacula constricta

Abstract: Sinonovacula constricta has been widely used as a health food and medicine in China, Japan, and Korea. In the present study, a water-soluble polysaccharide fraction (SCP-1) was prepared from S. constricta by enzyme-assisted extraction and purification of chromatography with DEAE-52 cellulose anion-exchange column and Sephadex G-100 size exclusion column. On the basis of the analytical results of high-performance liquid chromatography, Fourier transform-infrared spectroscopy, methylation analysis, and NMR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(49 citation statements)
references
References 71 publications
3
46
0
Order By: Relevance
“…() found that after treatment with the polysaccharide CMPB90‐1 from Cordyceps militaris at 250 to 500 μg/mL, a stimulated significant NO production in RAW 264.7 macrophages was observed and the level of production was similar to that production stimulated by LPS at 1 μg/mL. NO can be used as a quantitative index of macrophage activation and plays a pivotal role in host defense against invading microbes and tumors (Park et al., ; Yuan et al., ). Thus, this result indicated that KOS had a good effect on macrophage activation.…”
Section: Resultsmentioning
confidence: 99%
“…() found that after treatment with the polysaccharide CMPB90‐1 from Cordyceps militaris at 250 to 500 μg/mL, a stimulated significant NO production in RAW 264.7 macrophages was observed and the level of production was similar to that production stimulated by LPS at 1 μg/mL. NO can be used as a quantitative index of macrophage activation and plays a pivotal role in host defense against invading microbes and tumors (Park et al., ; Yuan et al., ). Thus, this result indicated that KOS had a good effect on macrophage activation.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of macrophages can enhance their antitumor activity through secretion of cytokines or regulation of the immune system [ 29 ]; thereby, it is commonly assessed to examine the immunomodulatory function of polysaccharides [ 21 , 30 ]. In this study, macrophage immunological activity assay revealed that RS-3-1, BZ-3-1, FL-3-1, and GC-3-1 could enhance phagocytosis, promote NO production, and increase tumor necrosis factor (TNF- α ) level in RAW 264.7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, DPPY-0.5 possessed the most potent immunostimulating activity among the four polysaccharides. The immunomodulating activity of polysaccharides was found to be significantly influenced by their chemical compositions (Yuan et al, 2015). Sulfated polysaccharides have been demonstrated to possess superior immunomodulatory activity via in vitro and in vivo studies (Di et al, 2017;Kim et al, 2011).…”
Section: Effect On the Secretion Of No In Raw2647 Cellsmentioning
confidence: 99%